Fungal sensitisation in severe asthma is associated with the identification of Aspergillus fumigatus in sputum. (8th August 2016) - Farrant, John; Brice, Henry; Fowler, Stephen; Niven, Robert
Abstract: Background : Fungal sensitisation is an important factor in severe asthma, not only for allergic bronchopulmonary aspergillosis (ABPA) but also the more recently described severe asthma with fungal sensitisation (SAFS). It is not known whether these diseases are driven by the presence of airway fungal colonisation. We aimed to determine if both SAFS and ABPA were associated with airway isolation of Aspergillus fumigatus and whether the frequency of isolation changed following anti-fungal treatment. Methods : Sputum samples were collected from patients with SAFS, ABPA and a control group without fungal sensitisation. We recorded details of antifungal treatment, serum IgE and A. fumigatus specific IgE levels. In a subgroup ( n = 9) we recorded serial sputum PCR measurements before and during itraconazole therapy. Results : 244 sputum samples were provided by 135 patients, 41(17%) ABPA, 168(69%) SAFS, and 35(14%) controls. Sputum Aspergillus fumigatus PCR was positive in 61 SAFS patients (70%) and 6 ABPA patients (50%) not on anti-fungal treatment at the time of the test, compared to 3 (9%) in controls (χ 2 = 37.90, p < 0.001). Consequently, 19 patients with SAFS who were taking antifungal treatment (23%) were significantly less likely to be PCR positive than the 61 patients not on treatment (70%) (χ 2 = 36.66, p < 0.001). All 9 patients assessed serially during therapy had positive sputum PCR pre-treatment and all became negative during itraconazole treatment. Conclusion : We have shown that isolation of fungus from the airway of severe asthma patients with fungal sensitisation is very common, supporting the hypothesis of a mechanistic link between fungal colonisation and sensitisation.